Pelatihan Pengelolaan Risiko Koperasi dalam Meningkatkan Kapasitas Pengurus dan Anggota Koperasi Merah Putih - Daniel Kartika Adhi; Panca Wahyuningsih; Nurrohmi Ambar Tasriastuti (Fokus ABDIMAS, 2026)
This community service activity aims to enhance the understanding and capacity of cooperative managers and members in risk management. The activity was conducted in the form of a workshop using a participatory approach at the Sekolah Tinggi Ilmu Ekonomi (STIE) Pelita Nusantara on April 8, 2026, with a total of 30 participants. The methods employed included lectures, interactive discussions, case studies, and simulations. Evaluation was carried out through pre-tests and post-tests to measure the improvement in participants' understanding. The results showed an increase in the average score from 6.10 to 11.80, representing a percentage increase of 93.44% and an N-Gain value of 0.64. Statistical tests indicated that this improvement was significant. Additionally, participants demonstrated an enhanced ability to identify cooperative risks and develop simple mitigation steps. This activity proves that the workshop method is effective in improving participants' understanding and skills in cooperative risk management.  Keywords: risk management, cooperative, workshop, community service, internal control